Determinants Of The Proportion Of Tabarru' Funds In Indonesian Sharia General And Life Insurance For The 2018-2022 Period - Anasang Diskan Poetra; Nur Dhani Hendranastiti (UNIVED Press, 2024)
This study examines the impact of claim expense ratio, commission expense ratio, total assets, and investment profit sharing income ratio on the proportion of tabarru' funds in general and life Islamic insurance in Indonesia, both sharia and full-fledged business units. The aim is to recognise the factors that influence the allocation of tabarru' funds and how it affects the financial performance of the company. Using panel data regression analysis, this study found that the claims expense ratio has a significant positive impact on full-fledged insurers, while the commission expense ratio has a significant positive effect on the combined model and Islamic business units. In contrast, total assets negatively affect the proportion of tabarru' funds significantly in the combined model and Islamic business units, but not significantly in full-fledged insurers. The investment profit-sharing income ratio does not show a significant effect in all models. These results provide useful insights for the financial management of Islamic insurance companies in designing effective tabarru' fund allocation policies, especially during the transition period from Islamic business units to full-fledged Islamic insurance companies.